2022
DOI: 10.1021/acsami.2c06227
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Acoustic Metamaterial for Penetrating Aberration Layers

Abstract: Impedance-matched acoustic materials were developed to improve ultrasound penetration through the aberration layer. The traditional ultrasound layer matching material is called a couplant, which can only enhance ultrasound transmission to soft biological media such as the cartilage and muscle but cannot penetrate hard media such as the bone. Here, we propose a phasemodulated complementary acoustic metamaterial based on the principle of impedance matching, which enables ultrasound to penetrate the bone, and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Recent advances in additive manufacturing have greatly enhanced the ability to fabricate acoustic metamaterials [15,16]. The problem of acoustic impedance mismatch has also started to be addressed by various groups using acoustic metamaterials [17][18][19][20]. Research work by [7,21,22] showed that graded impedance matching metamaterials can improve broadband energy transmission in high frequency (1-5 MHz) applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in additive manufacturing have greatly enhanced the ability to fabricate acoustic metamaterials [15,16]. The problem of acoustic impedance mismatch has also started to be addressed by various groups using acoustic metamaterials [17][18][19][20]. Research work by [7,21,22] showed that graded impedance matching metamaterials can improve broadband energy transmission in high frequency (1-5 MHz) applications.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Shen et al theoretically designed a complementary acoustic metamaterial (CMM) that effectively weakens the aberrating layer of the skull, resulting in enhanced transmission and reduced acoustic field distortion . Recently, Li et al proposed a phase-modulated complementary acoustic metamaterial (PCMM) to counteract the effects of impedance mismatches . Although the simulation and experimental results are encouraging, these metamaterial structures are often complex and rigid, requiring customization for different skull shapes and different frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The mass density ρ and the bulk modulus κ are the key constitutive parameters that affect sound waves in AMMs, and they correspond to the dielectric constant ϵ and magnetic permeability μ in electromagnetic metamaterials, respectively. Through the implementation of AMMs for two decades, unique physical phenomena and functions, which cannot be achieved by only modifying material properties, have been demonstrated [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%